A survey to assess the knowledge of adverse drug reactions and pharmacovigilance practices among undergraduate medical students, interns and postgraduate students in a tertiary care hospital - N., Mamatha; Nadaf, Reshma (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of the study was to evaluate the knowledge and attitude towards pharmacovigilance and adverse drug reaction (ADR) reporting among the undergraduates, interns and postgraduate students. Methods: This was a cross sectional study done among the undergraduates, interns and post graduate medical students at Karnataka Institute of Medical Sciences, Hubballi using a pre-validated questionnaire that included 20 questions to evaluate the participants knowledge and perception of ADR and pharmacovigilance. The questionnaire was distributed to the participants (n=606) after taking their informed consent. The data was compiled and evaluated as percentages. Results: About 52% of the participants were aware of pharmacovigilance and 38.7% knew about the purpose of pharmacovigilance programme of India. 51% of the participants have experienced ADRs during their professional practice out of which 23% have reported to the pharmacovigilance centre. The most common barrier for under-reporting was lack of time to report ADR among 34% of the participants. 31% of the participants felt that managing patient was more important than reporting ADRs. 29% of the participants gave the reason as lack of access to ADR reporting forms. 25% of the participants had difficulty to decide whether ADR has occurred or not. Conclusions: Our study strongly suggests a greater need to create an awareness among undergraduate medical students, interns and postgraduate students to improve the reporting of ADRs.